Analisis Potensi Unggulan Kabupaten Empat Lawang Menggunakan Alat Analisis Regional - Marini Wulandari; Muhammad Rizki; Sumiyarti Sumiyarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Empat Lawang Regency, once classified as a disadvantaged region, has made significant progress in improving the welfare of its population. This is reflected in the declining poverty rate and increasing Human Development Index (HDI). However, the region's economic growth, as measured by GRDP and GRDP per capita, lags behind other regions in Sumatera Selatan. This research seeks to pinpoint the key economic sectors driving Empat Lawang Regency's development by employing a combined analysis of LQ, Shift Share, and Tipology Klassen. The analysis results indicate that no sector can be unequivocally classified as a leading sector in Empat Lawang Regency. Nonetheless, several sectors such as agriculture, forestry, fisheries, wholesale and retail trade, also the other sectors exhibit potential for further growth. These findings underscore the importance of targeted policies and investments to stimulate economic growth and enhance the livelihoods of the local population.